2016
DOI: 10.1007/s11136-016-1388-1
|View full text |Cite
|
Sign up to set email alerts
|

Long-term health status as measured by EQ-5D among patients with metastatic breast cancer: comparison of first-line oral S-1 and taxane therapies in the randomized phase III SELECT BC trial

Abstract: PurposeThe goal of chemotherapy for metastatic breast cancer (MBC) is to prolong survival and maintain health-related quality of life. This study aimed to evaluate long-term health status of patients with MBC who participated in the phase III randomized SELECT BC trial.MethodsIn the SELECT BC trial, patients were randomly allocated to the S-1 or taxane (paclitaxel or docetaxel) arm. Health status was assessed by EQ-5D at pre-treatment, 3 and 6 months after randomization, and every 6 months thereafter to the ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 31 publications
(22 reference statements)
0
10
0
1
Order By: Relevance
“…At each point, assessment was conducted before the start of the next treatment cycle. Although the EQ-5D-3L assessment continued beyond 12 months in the SELECT BC study [ 19 ], we excluded that data in the present study because a few patients continued the study treatment during that period.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…At each point, assessment was conducted before the start of the next treatment cycle. Although the EQ-5D-3L assessment continued beyond 12 months in the SELECT BC study [ 19 ], we excluded that data in the present study because a few patients continued the study treatment during that period.…”
Section: Methodsmentioning
confidence: 99%
“…The aim of this study was to investigate the impact of AEs on health utility, measured using the EQ-5D-3L, in metastatic breast cancer patients receiving first-line chemotherapy. We previously reported the long-term EQ-5D-3L index results from the SELECT BC study, a Japanese multicenter, open-label, randomized, phase III study comparing the oral fluoropyrimidine derivative drug S-1 with taxane as first-line chemotherapy for metastatic breast cancer [ 19 ]. The results included health utility values before progression, after progression, and immediately before death.…”
Section: Introductionmentioning
confidence: 99%
“…Secondary outcomes included changes in patient-reported quality-of-life outcomes, margin status, re-excision rates, procedural time and physician satisfaction with the use of the MOLLI system. Patient-reported quality of life was measured at day 0 prior to implantation and at day 30 after implantation, using the validated EQ 5D-3L and EQ-VAS questionnaires [8,9]. Similarly, breast radiologists, breast surgeons and pathology assistants were asked to complete a short five-point Likert scale questionnaire to evaluate their experience using MOLLI immediately after their interaction with the system, or completion of their respective procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study examined longer-term (60 months) EQ-5D index values [ 26 ] and reported that the values were higher in the S-1 arm than the taxane arm when the analysis was limited to the first 12 months during progression-free survival (PFS). However, the values did not differ between arms when observations were continued up to 60 months.…”
Section: Discussionmentioning
confidence: 99%